THE CORRELATION BETWEEN MOTIVATION AND READING COMPREHENSION OF THE SECOND YEARS STUDENTS OF MAN 1 PEKANBARU - Dila Suryani; Fadly Azhar; M. Syarfi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This correlation research is aimed to find out the correlation of the students motivation with reading comprehension of the second year students of MAN 1 Pekanbaru. The research data were collected from July to August 2016. The subject of this research was class XI IPA 3, which consist of 30 students. The data were collected by giving a test to the students in the form of multiple choice test and questionnaire about motivation. The result of the research showed that the second year students of Man 1 Pekanbaru got mediocre level with the mean score of 49,67 in reading comprehension and enough category (67,8) in the students questionnaire of motivation. Therefore, it can be concluded that the correlation of the second year students of MAN 1 Pekanbaru in motivation and reading comprehension is high with rxy is 0,72.Key Words: Correlation, Motivation, Reading Comprehension